HUBUNGAN FUNGSI KOGNITIF DENGAN TINGKAT KEMANDIRIAN ACTIVITY DAILY LIVING (ADL) LANJUT USIA DI PANTI WERDHA - Novianto, Sahril; Ma’rifatul A, Lilik (JURNAL KEPERAWATAN BINA SEHAT, 2015)
Ageing process is a process of gradual disappearance of the networks ability to self-repair or replace and maintain normal function so it can not withstand the infection and repair the damage suffered. The process of aging can lead to many changes in one of them such as the decline in cognitive abilities like to forget, setbacks orientation to time, place, space, and not easily accept new things or ideas. The purpose of this study was to analyze the relationship of cognitive function with a degree of independence Activity Daily Living (ADL) in the elderly in UPT Werdha Mojopahit Mojokerto. Analytical research design correlation with cross sectional approach. The entire elderly population in UPT Werdha ‘Mojopahit’ Mojokerto as many as 45 people to obtain a sample of 30 people were taken by purposive sampling. Data taken with observation and interviews, using instruments Status MMSE and Barthel Index. After the data collected is done followed by data processing and statistical test of Rank Spearman with SPSS version 16.0. The results showed r (0,000) < a (0,05), so that means there is H0rejected Relations Cognitive Function with the Independence of Activity Daily Living (ADL) in the elderly in UPT Werdha ‘Mojopahit’ Mojokerto, with r=0.855, which means the correlation high, strong. However, the elderly are advised to have a mental and physical activity to maintain cognitive function and ADL their level of independence in order to stay under normal circumstances and not depend on others.Keywords:Cognitive Function,Activity Daily Living (ADL), Elderly